1992
DOI: 10.1021/np50087a002
|View full text |Cite
|
Sign up to set email alerts
|

Brominated Polyacetylenic Acids from the Marine Sponge Xestospongia muta: Inhibitors of HIV Protease

Abstract: The EtOAc extract of the sponge Xestospongia muta collected in Colombus Island, Bahamas, yielded eleven straight-chain unsaturated, polyacetylenic, brominated acids, seven of which were identified on the basis of spectral data, including the unknown acids 2-7. These acetylenic acids are the first known examples that have been shown to inhibit HIV protease, a critical enzyme in the replication of human immunodeficiency virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 8 publications
3
62
0
2
Order By: Relevance
“…The diacetylene-containing fatty acid 35G has been co-isolated with the structurally related trans-enyne 35A [368]. A later study found a series of brominated fatty acids with acetylenic groups at the 5, 7, 13, 15, and 17 positions (35D, 35H-K, 35N-O) [370]. In contrast to plant lipids, these brominated natural products contained exclusively trans-alkenes.…”
Section: Marine Fatty Acids Andmentioning
confidence: 99%
“…The diacetylene-containing fatty acid 35G has been co-isolated with the structurally related trans-enyne 35A [368]. A later study found a series of brominated fatty acids with acetylenic groups at the 5, 7, 13, 15, and 17 positions (35D, 35H-K, 35N-O) [370]. In contrast to plant lipids, these brominated natural products contained exclusively trans-alkenes.…”
Section: Marine Fatty Acids Andmentioning
confidence: 99%
“…Many natural products from marine organisms are currently under investigation for cancer and pain treatments (Newman and Cragg, 2004), but they are also of interest for their potential as novel anti-viral therapies (Gustafson et al, 2004). Numerous compounds derived from marine organisms have been shown to exhibit anti-HIV activity through targeting a variety of essential HIV-specific enzymes, including the viral protease (Patil et al, 1992). Hence, it was of interest to us to screen our marine extracts for SARS-CoV 3CL pro inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…L'acide 14,16-dibromohexadéca-7E,13E,15Z-trièn-5-ynoïque a été isolé d'une Xestospongia australienne (Schmitz et Gorichand, 1978). Les AG bromés des éponges Xestospongia et leurs esters ont une activité antibactérienne significative (Bourguet-Kondracki et al, 1992) et inhibent l'action de l'enzyme protéase jouant un rôle crucial dans la réplication du virus d'immunodéficience humaine (Patil et al, 1992). Les éponges des familles Nepheliospongia et Haploscleria produisent aussi des métabolites et des AG acétyléniques (Cimino et al, 1985).…”
Section: Ag Bromésunclassified